Barriers to liposomal gene delivery: From application site to the target - Saffari, M.; Moghimi, H.; Dass, Crispin (SHAHEED BEHESHTI UNIV, SCH PHARMACY, 2016)
Gene therapy is a therapeutic approach to deliver genetic material into cells to alter their function in entire organism. One promising form of gene delivery system (DDS) is liposomes. The success of liposome-mediated gene delivery is a multifactorial issue and well-designed liposomal systems might lead to optimized gene transfection particularly in vivo. Liposomal gene delivery systems face different barriers from their site of application to their target, which is inside the cells. These barriers include presystemic obstacles (epithelial barriers), systemic barriers in blood circulation and cellular barriers. Epithelial barriers differ depending on the route of administration. Systemic barriers include enzymatic degradation, binding and opsonisation. Both of these barriers can act as limiting hurdles that genetic material and their vector should overcome before reaching the cells. Finally liposomes should overcome cellular barriers that include cell entrance, endosomal escape and nuclear uptake. These barriers and their impact on liposomal gene delivery will be discussed in this review.